Prevalence of urogenital schistosomiasis among school-age children in Otamokun, Oyo State, Nigeria - Jaiyeola, T.M.; Akinsolu, F.T.; Musa, Z.A.; Olowolafe, T.A.; Iwu, V.O. (Elsevier, 2025)
Objectives Schistosomiasis is the second most serious parasitic disease in Nigeria after malaria, causing significant morbidity and mortality worldwide. Accurate, precise, reliable, sensitive, and specific diagnostic methods are required for the accurate detection of Schistosoma spp. and effective control. This study aimed to detect the prevalence of schistosomiasis and determine the presence of Schistosoma haematobium DNA in the urine samples of school-age children (SAC) in Otamokun, Oyo State, Nigeria. Methods A community-based cross-sectional study involving 165 SAC aged 5-17 years selected through multistage sampling was carried out. Urine microscopy was carried out to detect S. haematobium eggs, and S. haematobium DNA was isolated from the positive samples. The mitochondrial gene cytochrome oxidase subunit 1 was amplified using conventional polymerase chain reaction. Results S. haematobium eggs were found in 12 out of 165 (7.3%) urine samples after microscopy, 11 SAC had light infection, and one had moderate infection. S. haematobium DNA was identified in six of the samples after blast on the National Centre for Biotechnology Information database. Conclusion Urogenital schistosomiasis is still prevalent in Otamokun, even though in low levels. The study highlights differences between urine microscopy and molecular diagnostic methods, emphasizing the need to include molecular tools in accurate surveillance, especially in places with low prevalence.